1999
DOI: 10.1038/sj.onc.1202490
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2 regulates a caspase-3/caspase-2 apoptotic cascade in cytosolic extracts

Abstract: Apoptosis is accompanied by the activation of a number of apoptotic proteases (caspases) which selectively cleave speci®c cellular substrates. Caspases themselves are zymogens which are activated by proteolysis. It is widely believed that`initiator' caspases are recruited to and activated within apoptotic signalling complexes, and then cleave and activate downstream`eector' caspases. While activation of the eector caspase, caspase-3, has indeed been observed as distal to activation of several dierent initiator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(103 citation statements)
references
References 29 publications
6
97
0
Order By: Relevance
“…It recently was reported that caspase-2 activation might occur by oligomerization without any significant processing of procaspase-2 (33). Our data may implicate the activation of caspase-2 at an early stage without marked processing of the precursor, and its cleavage at the late stage may be a result of the activity of caspase-3 as suggested previously (34). This hypothesis remains to be tested.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…It recently was reported that caspase-2 activation might occur by oligomerization without any significant processing of procaspase-2 (33). Our data may implicate the activation of caspase-2 at an early stage without marked processing of the precursor, and its cleavage at the late stage may be a result of the activity of caspase-3 as suggested previously (34). This hypothesis remains to be tested.…”
Section: Resultssupporting
confidence: 76%
“…Nevertheless, although much remains to be deciphered about this caspase, recent work has demonstrated that caspase-2 plays critical and singular roles in the control of apoptosis induced by anti-Fas, cytokine deprivation, ␤-amyloid, etoposide, and other stress stimuli (36). Some studies show that initiator caspase-2 is involved in the early stage of apoptosis before mitochondrial dysfunction (11,13,14,36,37), whereas others show that caspase-2 acts downstream of mitochondria (34,38). The possible factors that regulate its activation are not fully understood.…”
Section: Resultsmentioning
confidence: 99%
“…27 Furthermore, in studies employing in vitro systems to study the events in the cytochrome c initiated caspase cascade, not only are the long-prodomain caspases -2, -8 and -10 activated in response to the Apaf-1-mediated activation of caspase-9, but their activation is dependent upon the actions of caspase-3, a short prodomain`effector' caspase. 30,56 These instances of the downstream activation of upstream' caspases have been further supported by the finding that the activation of caspases -2 and -8 is impaired in dexamethasone-induced apoptosis of thymocytes from APAF-1 or CASP-9 null mice. 57,58 It has also been demonstrated that following its activation by caspase-9, caspase-3 feeds back on caspase-9 thereby amplifying the cascade.…”
Section: Ampli®cation: Activation Of`downstream' Caspasesmentioning
confidence: 86%
“…Actually, caspases with a short prodomain can transactivate caspases with a long prodomain, e.g. to realize ampli®cation pathways (Swanton et al, 1999;Slee et al, 1999). In addition, several regulatory mechanisms that include transcriptional regulation of the enzymes (Droin et al, 1998;Kojima et al, 1998;Fujimura et al, 1999), posttranslational modi®cations (Dimmeler et al, 1997;Cardone et al, 1998), sub-cellular compartmentalization (Colussi et al, 1998;Susin et al, 1999a, Mancini et al, 2000 and interaction with adaptor or inhibitor molecules (for review: Kumar, 1999) modulate the caspase cascade.…”
Section: Discussionmentioning
confidence: 99%